Learning Evaluation in Overcoming Student Learning Problems - Mauzifa; Bambang Samsul Arifin; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2025)
This research reviews the concept of evaluation implementation as a solution to address student learning issues The integrated methods in this study include literature review, and then data collection through gathering and analyzing various relevant literature such as articles, books, and related materials The data is analyzed using qualitative descriptive techniques, and the results are interpreted scientifically and rationally The findings of this research indicate that evaluation is an integral part of the learning process, providing a positive impact in addressing student learning issues and improv the quality of the process learning and outcomes with enhancement Continuous evaluation is carried out by identifying the characteristics of learning problems comprehensively, from the aspects and components of learning, namely students, educators, resources, and learning environments Evaluation can be used as a reflection of learning, which can then serve as a guide for educators in taking action towards teaching processes by considering the suitability and success of a learning experience